(untitled) (Journal of Nepalese Business Studies, 2021)
In Nepalese society, female people feel that they are facing many obstacles in their career development such as individual, family, organization barriers, etc. In this regard, this study is conducted to analyze barriers in female career development. So, the study’s main objective is to analyze the impact of individual and family barriers on female school teachers’ career development. ausal effect research design has been employed in this study to analyze the impact of the barriers on female career development. The study used a judgmental sampling technique to gather the real picture of data from female school teachers in Kathmandu valley. Multiple regression analysis techniques has been adopted to analyze the data. From the result of data analysis, it is concluded that the family issue has hampered the career development of female school teachers. This means that Nepalese female teachers have to do their office duty along with giving time for their family members, housework and child-caring, etc. This could be beneficial to school administrators, trainers, and human resource professionals who want to help female teachers for the advancement of their careers.